Using Technology to Facilitate Faculty Evaluation - Theresa Glenn; Rise' Lara (Academic Chairpersons Conference Proceedings, 2019)
Are you tired of carrying a dozen or more 3-ring binders around to evaluate your faculty’s portfolios? Well say no more to the traditional faculty portfolio and go paperless. With the advent of Google sites, one department has streamlined the portfolio process with each faculty member having their own portfolio Google site.
Keywords: Portfolios; evaluation; technology; e-portfolios; reviews